Early detection of skin cancer: experience of a skin cancer prevention campaign in Piauí-Brazil - Rafael Bandeira Lages; Patrícia Barros Barbosa; Isabella Parente Almeida; Lauro Rodolpho Soares Lopes; Lauro Lourival Lopes Filho (Universidade de Fortaleza, 2012)
Objectives: To evaluate the correlation between the diagnoses of skin cancer and known risk factors through analysis of data from the National Skin Cancer Prevention Campaign held by Brazilian Society of Dermatology in the state of Piauí, Brazil, in recent years. Methods: Cross-sectional descriptive and analytical report using quantitative data obtained from a prevention campaign in the state of Piauí, in 2009 and 2010. Collected data was submitted to a descriptive analysis, and multivariate logistic regression, using as dependent variable the skin cancer diagnosis. Results: In 2009 and 2010, this campaign was responsible for 1141 consultations, diagnosing 122 (10.7%) cases of skin cancer: 108 basal cell carcinomas (BCC), 10 squamous cell (SCC) and four melanomas. Of those examined, 35.4% were male, 73.1% reported inadequate sun protection, 16.4% had a family history of skin cancer and 7.2% had personal history. Those with history of skin cancer were 5.24 times more likely to have a new diagnosis of cancer, while those presenting non-black skin were 4.91 times more likely to diagnosis. Conclusion: Personal or family history of epithelial neoplasia, non-colored black skin and the male gender were associated to higher chances of developing skin cancer. In addition, unprotected sun exposure remains routine.